2020
DOI: 10.1093/cdn/nzaa044_018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Dietary Inflammatory Index Over Time and Cancer Development Within Rural Post-Menopausal Women

Abstract: Objectives The objective of this study was to determine the extent to which diets with a higher inflammatory potential, as measured by the Dietary Inflammatory Index (DII), are associated with cancer development in a cohort of rural post-menopausal women. Methods This study was a secondary analysis of participants of a randomized control trial evaluating the effect of vitamin D and calcium supplementation on cancer developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the same cohort, women with dietary changes towards, or a history of, pro-inflammatory diets had a higher risk of colon cancer compared with those in the anti-inflammatory stable group, particularly for proximal colon cancer (for proinflammatory change, HR = 1•32, 95 % CI 1•01, 1•74) and among non-users of non-steroidal anti-inflammatory drugs (for proinflammatory stable, HR = 1•42, 95 % CI 1•01, 2•03) (14) . Proinflammatory change in diet has been reported in a small cohort of Australian women (aged 51-62 years at baseline, -0•60 to -0•46 over 14 years) (25) and in rural postmenopausal women (55 years or older) in Nebraska over 4 years, which was larger in participants who developed cancer than in those without cancer (26) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the same cohort, women with dietary changes towards, or a history of, pro-inflammatory diets had a higher risk of colon cancer compared with those in the anti-inflammatory stable group, particularly for proximal colon cancer (for proinflammatory change, HR = 1•32, 95 % CI 1•01, 1•74) and among non-users of non-steroidal anti-inflammatory drugs (for proinflammatory stable, HR = 1•42, 95 % CI 1•01, 2•03) (14) . Proinflammatory change in diet has been reported in a small cohort of Australian women (aged 51-62 years at baseline, -0•60 to -0•46 over 14 years) (25) and in rural postmenopausal women (55 years or older) in Nebraska over 4 years, which was larger in participants who developed cancer than in those without cancer (26) .…”
Section: Discussionmentioning
confidence: 92%
“…The inflammatory potential of the diet, as estimated by the E-DII, has been consistently associated with disease outcomes and mortality (6)(7)(8)(9)(10)(11)(12) . However, there are only few studies that have contributed additional evidence by examining longitudinal changes in the inflammatory potential of diet (13,14,(24)(25)(26) . In the Women's Health Initiative Observational Study where FFQ were repeated among postmenopausal women (aged 50-79 years at baseline), mean E-DII score decreased modestly from -1•14 at baseline to -1•50 at Year 3 representing a transition towards an anti-inflammatory diet (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both the Dietary Inflammatory Index (DII) and Mean Adequacy Ratio (MAR) include micronutrients, but their intakes are related to different end-points, namely the risk of effect on inflammatory markers [ 27 ] or the actual micronutrient Recommended Dietary Allowances of the individual [ 28 ], respectively. The DII has been used to assess changes in dietary quality over time [ 29 , 30 , 31 ], but no studies using the MAR were found in the current literature.…”
Section: Introductionmentioning
confidence: 99%